Prevalence and determinant factors of Chronic Energy Deficiency (CED) in pregnant women - Harna Harna; Rahmawati Rahmawati; Andi Muh Asrul Irawan; Mertien Sa’pang (AcTion: Aceh Nutrition Journal, 2024)
Pregnant women with Chronic Energy Deficiency (CED) are prone to malnutrition due to prolonged imbalances in the intake of essential nutrients. This study aimed to analyze the factors associated with the risk of CED in pregnant women. This study had a quantitative, cross-sectional design and was conducted from June to August 2023 in the working area of the Parung Panjang Health Center, Bogor Regency. The sample size in this study was 140 pregnant women using purposive sampling. The respondents’ characteristics were obtained through questionnaire interviews. MUAC was collected through MUAC tape, dietary intake using a Semi-Quantitative Food Frequency Questionnaire (SQ-FFQ) form, and hemoglobin through a rapid test. Analysis was performed using the chi-square statistical test at 95% CI. The results of this study showed that the prevalence of CED was 20,7%. There was a significant relationship between maternal age, parity, gestational age, history of infectious diseases, knowledge, energy, and protein adequacy and CED in pregnant women (p <0,05). There was no significant relationship between income, anemia status, fat and carbohydrate adequacy, and the occurrence of CED (p> 0,05). In conclusion, the determinants of CED include maternal age, parity, gestational age, history of infection, knowledge, energy, and protein intake.